Biallelic ATOH1 Gene Variant in Siblings With Pontocerebellar Hypoplasia, Developmental Delay, and Hearing Loss. (3rd June 2022) - Višnjar, Tanja; Maver, Aleš; Writzl, Karin; Maloku, Ornela; Bergant, Gaber; Jaklič, Helena; Neubauer, David; Fogolari, Federico; Pečarič Meglič, Nuška; Peterlin, Borut
Abstract : Background and Objectives: To report on the novel association of biallelic variant in atonal basic helix-loop-helix transcription factor 1 ( ATOH1 ) gene and pontocerebellar hypoplasia (PCH), severe global developmental delay, intellectual disability, and hearing loss in a family with 2 affected siblings. Methods: A detailed clinical assessment and exome sequencing of peripheral blood sample were performed. Segregation analysis with Sanger sequencing and structural modeling of the variant was performed to support the pathogenicity of the variant. Results: A homozygous missense variant (NM_005172.1:c.481C>G) in the ATOH1 gene was identified in the proband and his affected sister. The segregation analysis subsequently confirmed its segregation with an apparently recessive PCH in this family. ATOH1 encodes for the atonal basic helix-loop-helix (bHLH) transcription factor 1, a core transcription factor in the developing cerebellum, brainstem, and dorsal spinal cord, and in the ear. The identified variant results in the p.(Arg161Gly) amino acid substitution in the evolutionarily conserved DNA-binding bHLH domain of the ATOH1 protein. Biallelic missense variants in this domain were previously reported to result in disordered cerebellar development and hearing loss in animal models. In silico homology modeling revealed that p.Arg161Gly in ATOH1 protein probably disrupts a salt bridge with DNA backbone phosphate and increases the flexibility of the bHLH helix–both of which together affect the binding capability of the bHLH domain to the DNA. Discussion: Based on the sequencing results and evidence from structural modeling of the identified variant, as well as with previous reports of ATOH1 gene disruption, we conclude that ATOH1 may represent a novel candidate gene associated with the phenotype of PCH, global developmental delay, and hearing loss in humans.